2023
DOI: 10.3390/ijms24020984
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Common Risk Factors with Polygenic Scores Improves the Prediction of Type 2 Diabetes

Abstract: We tested associations between 13 established genetic variants and type 2 diabetes (T2D) in 1371 study participants from the Volga-Ural region of the Eurasian continent, and evaluated the predictive ability of the model containing polygenic scores for the variants associated with T2D in our dataset, alone and in combination with other risk factors such as age and sex. Using logistic regression analysis, we found associations with T2D for the CCL20 rs6749704 (OR = 1.68, PFDR = 3.40 × 10−5), CCR5 rs333 (OR = 1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Expression of CX3CL1 by human adipocytes and stromal vascular cells has been correlated with obesity, insulin resistance, and diabetic mellitus. 16 Previously it was found that rheumatoid arthritis patients' synovial fluid had higher levels of CX3CL1 than healthy individuals. In rheumatoid arthritis, CX3CL1 drives T celldependent proliferation of synovial fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CX3CL1 by human adipocytes and stromal vascular cells has been correlated with obesity, insulin resistance, and diabetic mellitus. 16 Previously it was found that rheumatoid arthritis patients' synovial fluid had higher levels of CX3CL1 than healthy individuals. In rheumatoid arthritis, CX3CL1 drives T celldependent proliferation of synovial fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This study detected polymorphisms that were not included among those playing an important role as a risk factor in a previous report. 2 In addition, we noticed that there were several types of adipokine serums detected in their study, such as adiponectin, adipsin/factor D, lipocalin, total PAI-1, and resistin. 3 However, a previous study stated that circulating aprosin, the adipokine serum, was reviewed as a promising candidate for both novel pharmacological treatment strategies and diagnostic tools in clinical cases of diabetes mellitus.…”
Section: Dear Editormentioning
confidence: 92%
“…In addition, a previous study mentioned that the polymorphism of ADIPOQ rs17366743 was one of the integrating common risk factors, besides CCL20 rs6749704, TCF7L2 rs114758349, and CCL2 rs1024611, associated with the prediction of type 2 diabetes on the Eurasian continent. 2 …”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is defined by the World Health Organization (WHO) as a metabolic disorder of multiple etiologies characterized by chronic hyperglycemia with disturbances in carbohydrate, lipid, and protein metabolism resulting from defects in insulin secretion, insulin action, or a combination of both ( Timasheva et al, 2023 ). According to reports from the International Diabetes Federation, the prevalence of diabetes may continue to rise from 537 million in 2021 to 783 million in 2045 ( Mohammed et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%